Excess iodide downregulates Na+/I− symporter gene transcription through activation of PI3K/Akt pathway - Serrano Nascimento, Caroline (2016)
Transcriptional mechanisms associated with iodide-induced downregulation of NIS expression remain uncertain. Here, we further analyzed the transcriptional regulation of NIS gene expression by excess iodide using PCCl3 cells. NIS promoter activity was reduced in cells treated for 12-24 h with 10-5 to 10-3 M NaI. Site-directed mutagenesis of Pax8 and NF-κB cis-acting elements abrogated the iodide-induced NIS transcription repression. Indeed, excess iodide (10-3M) excluded Pax8 from the nucleus, decreased p65 total expression and reduced their transcriptional activity. Importantly, p65-Pax8 physical interaction and binding to NIS upstream enhancer were reduced upon iodide treatment. PI3K/Akt pathway activation by iodide-induced ROS production is involved in the transcriptional repression of NIS expression. In conclusion, the results indicated that excess iodide transcriptionally represses NIS gene expression through the impairment of Pax8 and p65 transcriptional activity. Furthermore, the data presented herein described novel roles for PI3K/Akt signaling pathway and oxidative status in the thyroid autoregulatory phenomenon.